2021
DOI: 10.3390/jof7121099
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Virulence of Candida albicans by Staphylococcus aureus: Evidence in Clinical Bloodstream Infections and Infected Zebrafish Embryos

Abstract: Coinfection with Candida and Staphylococcus results in higher mortality in animal studies. However, the pathogenesis and interplay between C. albicans and S. aureus in bloodstream infections (BSIs) is unclear. This study determines the clinical features and outcomes of mixed C. albicans/S. aureus (CA/SA) BSIs and biofilm formation on pathogenesis during coinfection. Demographics and outcomes for mixed BSIs and monomicrobial candidemia were compared. Compared to 115 monomicrobial C. albicans BSIs, 22 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…5A-B). This agrees with the lethal synergism observed from in vivo experiments of systemic and local infections after co-inoculation of both microorganisms (3, 911, 19, 20). Our results showed that G. mellonella larvae survival at 24 h decreased from 71.4% when infected with colony 8 to 0- 14% when infected with colonies 1 and 2, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5A-B). This agrees with the lethal synergism observed from in vivo experiments of systemic and local infections after co-inoculation of both microorganisms (3, 911, 19, 20). Our results showed that G. mellonella larvae survival at 24 h decreased from 71.4% when infected with colony 8 to 0- 14% when infected with colonies 1 and 2, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In the case of C. albicans and S. aureus, it has long been known that their intraperitoneal coinfection has a synergistic effect on mouse mortality (9). Increased virulence of C. albicans and S. aureus co-infection has also been reported in zebrafish embryos, Galleria mellonella larvae, and patients with systemic infections (10,11). However, it was only recently that the major lethality driver and its mechanism of activation were identified.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the majority of these patients (55.9%) were under treatment in the intensive care unit. It has been reported in previous studies that being in the intensive care unit will adversely affect both the risk of conversion to BSI of colonization, morbidity and mortality, since it indicates the presence of intravascular medical equipment applications, intensive drug therapy applications, and possibly underlying comorbidities that may be immunosuppressive 5,[17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…lead to higher morbidity and mortality than those caused by monomicrobial or polybacterial pathogens. 14 Pathogenic bacteria in the bloodstream release toxins and metabolites, thus provoking a systemic in ammatory response. 15 At present, procalcitonin (PCT) and C-reactive protein (CRP) are commonly used as in ammatory markers for the early diagnosis of BSIs.…”
mentioning
confidence: 99%